Sedimentation Processes on the Atlantic Southeastern United States Contintental Shelf - Pilkey, Orrin (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1968)
In lieu of presenting a summary of activities of the Duke University Marine Geology Program, a summary of scdimentological conclusions concerning the S. E. U. S. Atlantic shelf is presented. These conclusions are based in large part on term papers anri thesis projects carried out by geology students at Duke University.